Import competition and the composition of firm investments - Philippe Fromenteau; Jan Schymik; Jan Tscheke (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2016)
We study how foreign competition affects the composition of investments inside firms. A parsimonious model predicts that firms have an incentive to shift their investments towards more short-term assets when exposed to tougher competition. Using data on expenditures of listed US companies into various asset classes with different lifespans, we document empirical evidence that is consistent with this prediction. Over a fifteen year period between 1995 and 2009, the rise in import competition is associated with a reduction of the firm-specific asset lifespan by about 4.5% on average. We additionally exploit the Chinese WTO accession as an exogenous shock in firm expectations about future exposure to competition.
urn:nbn:de:bvb:19-epub-29654-5
Keywords: F14; F36; F65; G32; L20; D22; 330; import competition; firm investment behavior; investment life-span; shorttermism